GR_GERICHTE ZR2 2025 13 vom 29. Juli 2025 , Z01_ENT_ZPO_Vollausfertigung_20250730_153600_ANOM.docx - GR Gerichte (2025)
vorsorgliche Massnahmen (Art. 961 Abs. 1 Ziff. 1 ZGB) | OR 184-252 Kauf/Tausch/Schenkung